Outcome of patients with nonspecific pleuritis/fibrosis on thoracoscopic pleural biopsies. - Davies, H; Nicholson, J; Rahman, N; Wilkinson, E; Davies, R; Lee, Y (2010)
OBJECTIVE: Medical thoracoscopy is recommended in the investigation of patients with exudative pleural effusions, especially when pleural fluid analysis is uninformative. The histological finding of 'nonspecific pleuritis/fibrosis' is common in thoracoscopic biopsies and presents a great uncertainty for clinicians and patients as the long-term outcome of these patients is unclear, and anxieties about undiagnosed malignancy persist. METHOD: A retrospective case-note study of 142 patients who underwent medical thoracoscopy over a 58-month period in a tertiary referral centre with a high incidence of mesothelioma. Patients with 'nonspecific pleuritis/fibrosis' were followed up until death or for a mean (±SD) period of 21.3 (±12.0) months. RESULTS: A definitive histological diagnosis was achieved in 98 (69%) patients. A total of 44 (31%) patients had 'nonspecific pleuritis/fibrosis'. Five (12%) were subsequently diagnosed with malignant pleural disease after a mean interval of 9.8 (±4.6) months. All five patients had histologically confirmed mesothelioma. In 26 patients with 'nonspecific pleuritis/fibrosis', no cause for the pleural effusion was discovered. The false-negative rate of thoracoscopic biopsy for the detection of pleural malignancy was 5%, with a diagnostic sensitivity of 95% and negative predictive value of 90%. Pleural effusion recurrence was more frequently associated with a false-negative pleural biopsy result. However, there was no correlation with other patient characteristics or the thoracoscopist's prediction based on macroscopic appearances. CONCLUSION: Thoracoscopic pleural biopsy is valuable in the diagnosis of pleural malignancies. Patients with 'nonspecific pleuritis/fibrosis' require follow-up as a malignant diagnosis (especially mesothelioma) may eventually be established in approximately 12% of cases.